STRENGTHENING TOLERANCE BASED ON RELIGIOUS EDUCATION THROUGH MULTICULTURAL COMMUNICATION IN PRIMARY SCHOOLS - Afandi; Siri, Abu; Bhattacharya, Shilpi (STAI Ma'had Aly Al-Hikam Malang, 2025)
This research aims to analyze and develop a strategy for strengthening tolerance based on religious education through a multicultural communication approach in Primary Schools. In the context of Indonesia's diverse society, religious education plays a crucial role in fostering mutual respect and reinforcing the values of togetherness among students. This study employs a mixed-methods approach, combining qualitative and quantitative methods, to explore the relationship between religious instruction, tolerance, and intercultural communication in schools. Quantitative data were obtained through student surveys to measure their level of tolerance, while qualitative data were collected through in-depth interviews with teachers and students to understand the dynamics of multicultural communication in religious teaching. The research findings indicate that the integration of tolerance values into religious subject matter, supported by effective multicultural communication, can enhance students' understanding and acceptance of cultural diversity within the school environment. Furthermore, this study also reveals that inclusive communication strategies and multicultural-based teaching materials have a positive impact on students' attitudes towards differences. These findings are expected to serve as a reference for developing religious education programs that not only build students' spiritual depth but also strengthen harmony and social solidarity in a pluralistic society.